Curcumin Blocks Cytotoxicity of Enteroaggregative and Enteropathogenic Escherichia coli by Blocking Pet and EspC Proteolytic Release From Bacterial Outer Membrane - Sanchez-Villamil, Javier I.; Navarro-Garcia, Fernando; Castillo-Romero, Araceli; Gutierrez-Gutierrez, Filiberto; Tapia, Daniel; Tapia-Pastrana, Gabriela (Frontiers in Cellular and Infection Microbiology, 2019)
Pet and EspC are toxins secreted by enteroaggregative (EAEC) and enteropathogenic (EPEC) diarrheagenic Escherichia coli pathotypes, respectively. Both toxins are members of the Serine Protease Autotransporters of Enterobacteriaceae (SPATEs) family. Pet and EspC are important virulence factors that produce cytotoxic and enterotoxic effects on enterocytes. Here, we evaluated the effect of curcumin, a polyphenolic compound obtained from the rhizomes of Curcuma longa L. (Zingiberaceae) on the secretion and cytotoxic effects of Pet and EspC proteins. We found that curcumin prevents Pet and EspC secretion without affecting bacterial growth or the expression of pet and espC. Our results show that curcumin affects the release of these SPATEs from the translocation domain, thereby affecting the pathogenesis of EAEC and EPEC. Curcumin-treated EAEC and EPEC did not induce significant cell damage like the ability to disrupt the actin cytoskeleton, without affecting their characteristic adherence patterns on epithelial cells. A molecular model of docking predicted that curcumin interacts with the determinant residues Asp1018-Asp1019 and Asp1029-Asp1030 of the translocation domain required for the release of Pet and EspC, respectively. Consequently, curcumin blocks Pet and EspC cytotoxicity on epithelial cells by avoiding their release from the outer membrane.